2023
DOI: 10.3389/fvets.2022.1051284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of image-based sow activity patterns reveals several associations with piglet survival and early growth

Abstract: An activity pattern describes variations in activities over time. The objectives of this study are to automatically predict sow activity from computer vision over 11 days peripartum and estimate how sow behavior influences piglet's performance during early lactation. The analysis of video images used the convolutional neural network (CNN) YOLO for sow detection and posture classification of 21 Large White and 22 Meishan primiparous sows housed in individual farrowing pens. A longitudinal analysis and a cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…In a study focused on the 24 hours around farrowing, Illmann et al 21 showed that the number of postural changes at farrowing was positively correlated with piglet growth on the rst day after birth. In the same population as in the current study, we showed that early growth (to D7) of piglets from sows that change postural more often to hide the udder on the day of farrowing is lower than that of sows that do not hide the udder 22 . While their growth is on average 250 g/d over lactation, the average weight gain of pure Meishan piglets during the rst week after birth was 110 g/d, and that of pure Large White piglets was 160 g/d.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…In a study focused on the 24 hours around farrowing, Illmann et al 21 showed that the number of postural changes at farrowing was positively correlated with piglet growth on the rst day after birth. In the same population as in the current study, we showed that early growth (to D7) of piglets from sows that change postural more often to hide the udder on the day of farrowing is lower than that of sows that do not hide the udder 22 . While their growth is on average 250 g/d over lactation, the average weight gain of pure Meishan piglets during the rst week after birth was 110 g/d, and that of pure Large White piglets was 160 g/d.…”
Section: Introductionsupporting
confidence: 69%
“…Conversely, the two breeds do not differ in their general behavior in the days after farrowing, as described in Girardie et al 22 . The same range of variation was observed for postural and standing activity.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations